Dinuclear Titanium Complexes with Sulfamide Ligands as Precatalysts for Hydroaminoalkylation and Hydroamination Reactions - Jaspers, Daniel; Saak, Wolfgang; Doye, Sven (Synlett, 2012)
A new dinuclear titanium sulfamide complex was synthesized from N,N′-diphenylsulfamide and Ti(NMe2)4 and used as a precatalyst for the intermolecular hydroaminoalkylation of alkenes as well as the intramolecular hydroamination of alkenes.
Keywords: alkenes; amines; homogeneous catalysis; sulfur; titanium